2019
DOI: 10.2147/ijwh.s196112
|View full text |Cite
|
Sign up to set email alerts
|

<p>Barriers and facilitators of follow-up among women with precancerous lesions of the cervix in Cameroon: a qualitative pilot study</p>

Abstract: Purpose This pilot study explores the barriers to adherence to follow-up among women with cervical precancer in urban Cameroon. While follow-up of women with a positive screening of cervical precancer is the most important aspect of cervical cancer secondary prevention, women with cervical precancer do not adhere frequently to recommended follow-up schedule in Cameroon. The aim of the study was to explore and describe the barriers and facilitators to follow-up for cervical precancer among women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…In a recent qualitative study conducted among WHP nurses and clients, payment for treatment was identified as one of the major barriers to same-day treatment and posttreatment follow-up. 14 In a "see and treat" program in Thailand, 98.5% (609/618) of the women with precancer received same-day treatment. 15 However, in this Thailand study, it is not clear whether the treatment was provided at no charge or the women had to pay for it.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent qualitative study conducted among WHP nurses and clients, payment for treatment was identified as one of the major barriers to same-day treatment and posttreatment follow-up. 14 In a "see and treat" program in Thailand, 98.5% (609/618) of the women with precancer received same-day treatment. 15 However, in this Thailand study, it is not clear whether the treatment was provided at no charge or the women had to pay for it.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated barriers to treatment uptake after screening for cervical cancer. A study in Cameroon found that the use of reminder phone calls coupled with peer counseling and navigation of women diagnosed with cervical precancer could be effective ways of improving adherence to follow‐up 22. The role of patient navigators in improving linkage to treatment after screening for cervical cancer has been highlighted in Tanzania 23,24…”
Section: Discussionmentioning
confidence: 99%
“…The literature on determinants of screening uptake in lower-resource settings has identified important factors including women's cervical cancer knowledge, perceived efficacy of screening, and beliefs about disease severity and susceptibility [13][14][15][16][17][18]. Women have also reported that their male partners influence cervical cancer screening decisions [13,[18][19][20][21][22][23][24], and the World Health Organization recommends male-targeted outreach as a way to increase cervical cancer screening uptake [25] however very little is known about men's perspectives on cervical cancer and screening approaches [26]. The limited literature on this topic indicates that men are not very knowledgeable about cervical cancer (including risk factors, symptoms and ways of screening or treating), and that despite general support for the concept of cancer prevention, some men have hesitations about their wives undergoing screening [27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%